2018
DOI: 10.1016/j.ebiom.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Regulate the Vascular Remodeling of Aortic Dissection Via the p38 MAPK-HSP27 Pathway Mediated by Soluble TNF-RII

Abstract: Increasing researches suggest that inflammatory response is involved in vascular remodeling, which plays an important role in the development of aortic dissection. Glucocorticoids have been widely used in the clinical practice due to its powerful and effective anti-inflammatory property. However, the potential relationship between glucocorticoids and aortic dissection was still obscure. This study sought to elucidate the effect of glucocorticoids on the development and progression of aortic dissection, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…As mentioned above, calcium channel blocker TL_HRAS26 which regulates calcium signals might act as a potential drug for ATAAD. A recent study showed that glucocorticoids regulate the vascular remodeling of aortic dissection, (Zhang et al, 2018) our results also indicated that hydrocortisone hemisuccinate might be a useful drug by activating glucocorticoid receptor. Previous research demonstrated that aorta samples are mainly made up of aortic smooth muscle cells, fibroblasts and endothelial cells.…”
Section: Discussionsupporting
confidence: 77%
“…As mentioned above, calcium channel blocker TL_HRAS26 which regulates calcium signals might act as a potential drug for ATAAD. A recent study showed that glucocorticoids regulate the vascular remodeling of aortic dissection, (Zhang et al, 2018) our results also indicated that hydrocortisone hemisuccinate might be a useful drug by activating glucocorticoid receptor. Previous research demonstrated that aorta samples are mainly made up of aortic smooth muscle cells, fibroblasts and endothelial cells.…”
Section: Discussionsupporting
confidence: 77%
“…The external aortic diameter of the mice was measured in three transverse sections using image J software (National Institutes of Health), as described previously [ 21 ].The ascending aorta was defined as the proximal 2-mm section from the ostium of the innominate artery, the aortic arch as the section between the ostia of the left common carotid artery and left subclavian artery, and the descending aorta as the distal 2-mm section from the ostium of the left subclavian artery.…”
Section: Methodsmentioning
confidence: 99%
“…Increased glucocorticoids reduce the marginalization, extravasation and local activation of macrophages, thereby inhibiting MMP-2 secretion and thus protecting collagen degradation. These findings indicate that glucocorticoids and TNF-sRII may be interesting targets for future AD intervention (Zhang et al, 2018).…”
Section: Macrophage-associated Factors That Protect Against Admentioning
confidence: 76%